2012
DOI: 10.5402/2012/351603
|View full text |Cite
|
Sign up to set email alerts
|

Common Dermatoses in Children Referred to a Specialized Pediatric Dermatology Service in Mexico: A Comparative Study between Two Decades

Abstract: Background. Skin diseases among pediatric patients differ from those in adults. Epidemiological studies are scarce, and those performed in Mexican population date back thirty years. It is likely that these diseases might have changed their frequency. Material and Methods. Retrospective study in first-time patients referred to a pediatric dermatology service between January 1994 and December 2003. Demographics and diagnosis were recorded and compared with the results of a previous study performed in the same in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 9 publications
(11 reference statements)
4
25
0
9
Order By: Relevance
“…In various studies reported by Negi et al, nevi range from 1.6 to 2.3%, which is consistent with the present study. In a study conducted by Ruiz -Maldonado R et al 13 , they were reported in about 2.3%, which is in correlation with present study. In present study, among nevi mongolian spot was most common.…”
Section: Distribution Of Pediatric Dermatosessupporting
confidence: 80%
“…In various studies reported by Negi et al, nevi range from 1.6 to 2.3%, which is consistent with the present study. In a study conducted by Ruiz -Maldonado R et al 13 , they were reported in about 2.3%, which is in correlation with present study. In present study, among nevi mongolian spot was most common.…”
Section: Distribution Of Pediatric Dermatosessupporting
confidence: 80%
“…Many western epidemiologic studies on pediatric skin diseases among PD clinic referrals found viral warts as the most common infectious diseases. 3,[8][9][10] In our study warts were especially common in school age children and adolescents. In a Dutch study, 11 carried among children of school age the prevalence of cutaneous warts was found to be 29%, and a similar British study found the prevalence rate as 33%.…”
Section: Discussionmentioning
confidence: 97%
“…Muchos estudios epidemiológicos occidentales sobre dermatosis entre los pacientes derivados a los consultorios de dermatología pediátrica hallaron que las verrugas virales son las enfermedades infecciosas más frecuentes. 3,[8][9][10] En nuestro estudio, este fue especialmente el caso en los niños de edad escolar y los adolescentes.…”
Section: Discussionunclassified
“…[2][3][4][5][6][7][8][9][10] De hecho, varían notablemente los patrones entre los distintos grupos etarios; por lo tanto, en el futuro, el campo de la dermatología pediátrica debería dividirse en dermatología neonatal, dermatología pediátrica y dermatología adolescente.…”
Section: Discussionunclassified